Parental state anxiety correlates with preoperative anxiety in Chinese preschool children. (3rd May 2016) - Cui, Xulei; Zhu, Bo; Zhao, Jing; Huang, Yuguang; Luo, Ailun; Wei, Jing
Abstract : Aim: Preoperative anxiety in children is largely dependent on age and is influenced by anxiety level in parents. The current study compared the level of preoperative anxiety in preschool children versus school‐aged children and its relationship with the state and trait anxiety of the parents. Methods: This study included 54 preschool children (2–5 years of age) and 48 school‐age children (6–12 years) scheduled to receive ear, nose and throat, plastic or ophthalmologic surgeries. Preoperative anxiety of children was assessed in the holding area immediately prior to the surgery using a modified Yale Preoperative Anxiety Scale (m‐YPAS). Compliance with anaesthesia induction was assessed using an Induction Compliance Checklist (ICC). The state and trait anxiety of the parent who accompanied the child was assessed using a State‐Trait Anxiety Inventory (STAI) questionnaire. Results: Both m‐YPAS and ICC scores were higher in preschool children than in school‐age children with significant correlation between the two measures. The STAI‐S score of parents was higher in the preschool group than in the school‐age group. No significant difference was found in STAI‐T score between the two age groups. Children's m‐YPAS score correlated with parental STAI‐T score in both groups ( rho  = 0.297, P  = 0.029 and rho  = 0.338, P  = 0.019, respectively) but only with STAI‐S score in the preschool group ( rho  = 0.400, P  = 0.003). Conclusions: Both preschool children and their parents are more anxious than school‐age dyads prior to surgery. The anxiety level of the children correlates with state anxiety of the parents in preschool children but not in school‐age children.